Continuous Leakage-Resilient Public-Key Encryption Scheme with CCA Security. (9th January 2017) - Zhou, Yanwei; Yang, Bo
Abstract: In recent years, much attention has been focused on designing provably secure public-key encryption (PKE) scheme in the presence of key-leakage. However, most of them are researched in the bounded-leakage model, and cannot keep their claimed security in the continuous leakage setting. What's more, most of traditional leakage-resilient PKE schemes cannot ensure that all of elements in ciphertext are random from the adversary's view, and any polynomial time adversary can get leakage on the secret key from the corresponding ciphertext. But, in the real world, an adversary can trivially break the security of PKE scheme under the continuous leakage attacks. To get an efficient PKE scheme which can keep its original security in the continuous-leakage model, we propose a new construction of chosen-ciphertext attacks secure PKE scheme, and whose security is based on the hardness of the classical decisional Diffie–Hellman assumption and the target collision resistance of the hash function. Our method not only can tolerate continuous leakage attacks on the secret key through key update operation, but also enjoys better performances, such as the round leakage parameter λ C ≤ log q − ω ( log k ) ( k is the security parameter, q is a big prime order of the underlying group.) is independent of the plaintext space, and has the constant size, also, any polynomial time adversary unable to obtain leakage on the secret key from the corresponding ciphertext, etc. Because of these good performance features, our proposal may have some significant value in the practical applications.